Analisis Penanganan Dan Penyelesaian Kasus Pertanahan Di Kantor Pertanahan Kabupaten Lampung Timur - Sambawa Ningrum, Herlina Ratna (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
This research highlights the issue of land rights as a fundamental issue in society. Implementation of Article 6 paragraph (1) of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases at the East Lampung Regency Land Office is the main focus. The research uses normative and empirical juridical methods with secondary and primary data from literature and field studies as well as qualitative juridical analysis. The results of the research are that the implementation of these provisions has been carried out but has not been optimal. Factors inhibiting the implementation of these provisions are: internal factors, lack of understanding by employees at the East Lampung Regency Land Office regarding the stages of resolving land cases, lack of coordination between each section in the East Lampung Regency Land Office, and the absence of employees who have competence as Mediator. . Meanwhile, external factors include pressure from the community who want their land problems to be resolved immediately, lack of socialization of existing regulations to the community, and the types of cases and conditions in the field